Comparative effectiveness of exercise interventions on arterial stiffness in individuals at risk for cardiovascular disease: a systematic review and network meta-analysis - Ruo-Shan Wu; Yan Zhang; Xin-Wang Yuan; Xin Yan; Xiao-Lei Fu (Frontiers in Cardiovascular Medicine)
BackgroundPrevious studies have shown that exercise can improve arterial stiffness (AS). However, it remains unclear which type of exercise is most effective for managing AS, particularly in individuals at high risk for cardiovascular diseases (CVD). This review aims to evaluate the effects of various exercises on AS and related variables in individuals at high risk for CVD.MethodsA comprehensive search strategy was employed to systematically explore MEDLINE (PubMed), Embase, Cochrane Library, EBSCOhost, and Web of Science to identify relevant studies. Inclusion criteria were: (1) randomized controlled trials; (2) participants with known CVD risk factors as per the American College of Sports Medicine guidelines; (3) interventions including interval training (INT), aerobic exercise (AE), resistance exercise, and combined exercise (CT); (4) control groups engaging in no intervention, routine care, or health education; (5) outcome measures of pulse wave velocity (PWV), systolic blood pressure (SBP), and diastolic blood pressure; and (6) studies published in English. Studies were assessed using the Cochrane risk of bias tool and analyzed with a random-effects network meta-analysis.ResultsThe review included 2,034 participants from 43 studies. Both CT [standardized mean difference (SMD) = −0.98, p < 0.001, I2 = 84%] and INT (SMD = −0.77, p < 0.001, I2 = 61%) significantly reduced PWV, but both showed considerable heterogeneity. INT (SMD = −0.382, p < 0.001, I2 = 45%) and AE (SMD = −0.369, p < 0.001, I2 = 43%) significantly reduced SBP. Surface under the cumulative ranking curve (SUCRA) showed that CT (SUCRA = 87.2) was the most effective for lowering PWV, while INT (SUCRA = 81.3) was the most effective for lowering SBP.ConclusionIn high-risk populations for CVD, CT was most effective in improving AS, while INT demonstrated the greatest reduction in SBP. AE showed greater benefits at moderate to low intensities. Due to significant heterogeneity in CT, its results should be interpreted with caution. Further research with larger sample sizes is needed to confirm these findings.